Associations between frailty trajectories and cardiovascular, renal, and mortality outcomes in chronic kidney disease. Issue 5 (19th July 2022) - Wilkinson, Thomas J.; Miksza, Joanne; Zaccardi, Francesco; Lawson, Claire; Nixon, Andrew C.; Young, Hannah M.L.; Khunti, Kamlesh; Smith, Alice C.
Abstract: Background: Frailty is characterized by the loss of biological reserves and vulnerability to adverse outcomes. In individuals with chronic kidney disease (CKD), numerous pathophysiological factors may be responsible for frailty development including inflammation, physical inactivity, reduced energy intake, and metabolic acidosis. Given that both CKD and frailty incur a significant healthcare burden, it is important to understand the relationship of CKD and frailty in real‐world routine clinical practice, and how simple frailty assessment methods (e.g. frailty indexes) may be useful. We investigated the risk of frailty development in CKD and the impact of frailty status on mortality and end‐stage kidney disease (ESKD). Methods: A retrospective cohort study using primary care records from the Clinical Practice Research Datalink linked to Hospital Episode Statistics and the UK Office for National Statistics was undertaken in 819 893 participants aged ≥40 years, of which 140 674 had CKD. Frailty was defined using an electronic frailty index, generated electronically from primary care records. Cox proportional hazard and flexible parametric survival models were used to investigate the risk of developing frailty and the effect of frailty on risk of all‐cause and cardiovascular mortality, and ESKD. Results: The mean age of those with CKD was 77.5 (SD 9.7) years [61.0 (SD 12.1) years in no‐CKD group]; 62.0% of the CKD group were female (compared with 53.3% in no‐CKD group). The mean estimated glomerular filtration rate of those with CKD was 46.1 (SD 9.9) mL/min/1.73 m 2 . The majority of those with CKD (75.3%) were frail [vs. 45.4% in those without CKD (no‐CKD)]. Over 3 years (median), 69.5% of those with CKD developed frailty. Compared with no‐CKD, those with CKD had increased rates of developing mild (hazard ratio: 1.02; 95% confidence interval: 1.01–1.04), moderate (1.30; 1.26–1.34), and severe (1.50; 1.37–1.65) frailty. Mild (1.22; 1.19–1.24), moderate (1.60; 1.56–1.63), and severe (2.16; 2.11–2.22) frailty was associated with increased rates of all‐cause and cardiovascular‐related mortality (mild 1.35; 1.31–1.39; moderate 1.96; 1.90–2.02; and severe 2.91; 2.81–3.02). All stages of frailty significantly increased ESKD rates. Conclusions: Frailty is highly prevalent and associated with adverse outcomes in people with CKD, including mortality and risk of ESKD. Preventative interventions should be initiated to mitigate the development of frailty. The use of a simple frailty index, generated electronically from health records, can predict outcomes and may aid prioritization for management of people with frailty.